Minettes do Stock Monzonítico Glória Norte : evidência de magmatismo ultrapotássico pós-orogênico, com assinatura de subducção, no sistema orogênico sergipano - Fontes, Milena Prado (2017)
Lamprophyres occur as microgranular enclaves in the Glória Norte monzonitc Stock (588 ± 5 Ma) located in the central part of the Macururé Domain, Sergipano Orogenic System, in the Sergipe State. These lamprophric enclaves were classified as minettes and occur concentrated in an area approximately 1 km in diameter in the southeast region of the stock. The minettes present porphyritic textures (feldspars limited to matrix), panidiomorphic, granulation of the average matrix and correspond to syenites. The mafic minerals present in addition to the biotite are diopside, augite, hornblende and titanite. Perthitic orthoclase and andesine, biotite, carbonate, apatite, zircon are also present in the matrix. The chemical data of the minettes (K2O/Na2O>3, 6<%MgO>8, K2O>3%) indicates orogenic ultrapotassic magmatism (low Nb, Ta, Ti) and resulting from enriched mantle (Th/Yb>9 e 0.05<Ta/Yb<0.2). The information obtained in this study indicates that ultrapotassic mafic magmas were present during the post-tectonic event in the Sergipano Orogenic System.